2015
DOI: 10.1016/j.matdes.2015.08.129
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of friction stir welded joints made from ultrafine grained aluminium 1050

Abstract: In order to obtain ultrafine grained structure, commercially pure aluminium (Al 1050) plates were subjected up to 8 passes of Incremental Equal Channel Angular Pressing (IECAP) following route C. Plates in different stages of IECAP were joined using Friction Stir Welding (FSW). All welded samples were investigated to determine their mechanical properties and structure evolution in the joint zone. The joining process reduced mechanical strength of material in the nugget zone, which was explained by the grain gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 35 publications
(50 reference statements)
5
20
0
Order By: Relevance
“…On the other hand, when a relatively high level of tool tilt angle (5 • ) was applied, the un-bonded overlapped interface was forced toward the nipple region (indicated by the arrow in Fig. 5d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when a relatively high level of tool tilt angle (5 • ) was applied, the un-bonded overlapped interface was forced toward the nipple region (indicated by the arrow in Fig. 5d).…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have studied joining of 1XXX series aluminum and have found that FSW parameters have key roles in obtaining a sufficient joint performance and microstructural evolution [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[44] In addition, rapid necking is observed for samples with the UFG structure, which is typical for materials after the SPD processing, and has been achieved for pure aluminum. [21,45] The flow stress quickly achieves the maximum value and then decreases gradually. It indicates that necking occurs early and further deformation is accompanied by a deepening neck.…”
Section: B Mechanical Propertiesmentioning
confidence: 98%
“…This is especially common for materials, such as aluminum, which is characterized by high stacking fault energy. In our previous work, we have demonstrated that despite the deterioration of mechanical properties and grain growth in joints compared to hardened base material, good quality butt joints were produced using FSW for UFG aluminum plates. Moreover, the obtained results are promising in comparison to other methods of joining aluminum.…”
Section: Introductionmentioning
confidence: 99%